2020
DOI: 10.1016/j.clnu.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Arabinoxylan oligosaccharides and polyunsaturated fatty acid effects on gut microbiota and metabolic markers in overweight individuals with signs of metabolic syndrome: A randomized cross-over trial

Abstract: Background & Aims: Gut microbiota composition is linked to obesity and metabolic syndrome. The nutrients and doses required to modulate the gut microbiota towards beneficially influence components of the metabolic syndrome are unclear. This study aimed to investigate diet-induced effects on the gut microbiota and metabolic markers in overweight individuals with indices of the metabolic syndrome. Methods: A twelve-week randomized cross-over trial was conducted with two intervention periods separated by a washou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 55 publications
4
77
1
1
Order By: Relevance
“…Finally, we detected one negative correlation between MCP-1 values and OTU63 abundance ( ϭ Ϫ0. 35 and P ϭ 0.013).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, we detected one negative correlation between MCP-1 values and OTU63 abundance ( ϭ Ϫ0. 35 and P ϭ 0.013).…”
Section: Resultsmentioning
confidence: 90%
“…Further studies are, therefore, warranted to investigate this hypothesis in depth using in vivo study models in order to draw definitive conclusions about the potential and differential role of Blautia species in the management of obesity and its metabolic complications. For example, one of our previous intervention trials in overweight subjects indicates that intake of a wheat bran extract enriched in arabinoxylans boosts the proportion of Blautia species (34,35), suggesting that it is possible to design diet-based interventions to enrich the gut ecosystem with these bacterial species depleted in obese children. In spite of this, preclinical and clinical intervention trials with B. luti and B. wexlerae strains would be needed to definitively demonstrate their potential protective effect against obesity and prediabetic states.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first analyzing the effects of AXOS intake on gut microbiota composition by 16S rRNA sequencing in human. The main results demonstrated that AXOS exhibit the characteristic bifidogenic effect and promote the increase of a wide variety of butyrate producers [58].…”
Section: Arabinoxylans (Ax)mentioning
confidence: 93%
“…This study included cross-sectional baseline data from six human intervention trials: 3G, OPUS, DIOGENES, RIGHT, MyNewGut (MNG), and PROKA (1015). The studies were registered at http://www.clinicaltrials.gov; 3G (NCT01719913 and NCT01731366); SHOPUS (NCT01195610); DIOGENES (NCT00390637); RIGHT (NCT02358122); MNG: (NCT02215343); PROKA (NCT01561131) and approved by the Research Ethics Committees of the Capital Region of Denmark in accordance with Helsinki Declaration 3G (H-2-2012-064 and H-2-2012-065); SHOPUS (H-3-2010-058); RIGHT (H-1-2014-062); MNG (H-4-2014-052); and PROKA (H-2-2011-145) or the local ethical committees in the respective countries (16).…”
Section: Methodsmentioning
confidence: 99%